Protein and metabolite acclimations to temperature variability in a calcareous green macroalga Halimeda macroloba - Zhang, Hao; Wang, Yuyu; Zhang, Lingshuai; Wang, Zhiqin; Zhu, Zejun; Long, Lijuan (Frontiers in Marine Science, 2025)
IntroductionCoral reef ecosystems are undergoing significant restructuring due to climate-driven marine heatwaves. Understanding how calcareous macroalgae, the important primary producers and reef-builders, respond to temperature fluctuations is crucial.MethodsIn our study, we investigated the physiological and molecular responses of the green macroalga Halimeda macroloba to different temperatures (25, 28, 31°C) through quantitative proteomics and untargeted metabolomics analyses.Results and discussionH. macroloba showed an optimal growth at 28°C, with the highest levels of Chl a, calcium content, and photosynthetic efficiency. At the sub-optimal temperature of 25°C, the alga modulated its fatty acid composition to maintain membrane fluidity and accumulated selenium-containing metabolites to mitigate oxidative stress. At the supra-optimal temperature of 31°C, despite reduced photosynthetic performance, the alga maintained high metabolic activity to facilitate growth and calcification by increasing the abundance of proteins involved in light-harvesting, photosystems, and carbon fixation, while redistributing substantial carbon into sugars and fatty acids. Enhanced nitrogen reserves, shown by increased levels of nitrogen uptake and assimilation proteins and amino acids such as pyroglutamic and N-Methyl-D-aspartic acids, likely contributed to its high-temperature tolerance. These findings highlight the resilience of H. macroloba to moderate thermal stress and suggest its important implications for reef conservation and potential applications in aquaculture as ocean temperatures rise.